Trends of Women’s Participation in Economic Activity of Bangladesh: Status and Disparity - Kalam, Iftekhar Mohammad Shafiqul; Al Amin, Mohammad Mastak (European Scientific Journal, ESJ, 2016)
In Bangladesh - despite having significant progress in reducing poverty over the past three decades and increase in the number of women in the paid workforce, there remain many areas where gender disparities still exists. Study shows women’s earnings to be approximately 58.5% of men’s. Women in Bangladesh remain particularly vulnerable to live in poverty. Socially prescribed roles have limited women’s access to economic resources such as capital, skills, and marketing know how. However, social attitudes are changing, and women in Bangladesh are taking advantages of new opportunities for economic and social development with far reaching effects.